Penerapan Sistem Pembelian Dalam Kaitannya Dengan Sistem Pengeluaran Kas Guna Mencapai Efektivitas Pengendalian Intern - Marpaung, Annaria Magdalena (STIE Kesatuan, 2010)
Purchasing transactions in general can be categorized into two kinds: local purchasing and import purchasing.Local purchasing is a purchase from domestic suppliers, whereas import is from abroad. In making a purchase of goods at every company, purchase accounting system is needed in bringing about purchasing transaction. If purchasing system is not correct or controlled, the company willnot be stable in carrying out its daily operational activities.Purchasing system arranges ways to do all purchasings needed by the company. This system starts from goods needed up to goods purchased will have been received. The goal of this research is to evaluate purchasing system in connection with cash expenditure of a service company. The evaluation is done to find out whether the purchasing system established by the company has constituted a minimum opportunity to act deceitfulness in carrying out purchase, from goods needed up to goods received. In addition, the author evaluate as well how cash expenditure procedure to pay to the suppliers can be accounted for and can be avoided from deceitfulness. The research has been conducted by the author at PT Bogor Raya Development, located in Bogor. PT Bogor Raya is a company functioning as Property Services, Golf Club, Event Organizer, and Hotel & Resort. The result of this research shows that internal control on purchasing and cash expenditure system at PT Bogor Raya Development has not been good enough yet, there are opportunities to act deceitfulness at the system. The opportunities to act deceitfulness are able to be viewed from the convergence of purchasing function and receipt function. Besides, itâs found wasting, that is printing exit bank ducuments in triple, and the same two documents are kept at the same department. This constitutes a waste because printing requires cost that is not cheap. The evaluationâs result of this research shows that there are several points which are not applied at PT Bogor Raya Development. The procedure system has not been made in written by the company, with the result that sometimes it causes the employees feel confused: the tasks they do actually including their resposibility or not. In addition, the supervision on goods received has not been effective yet because purchasing function and goods acceptance are not separated. The supervision on goods in the warehouse has not been effective as well because itâs held by the employee of purchasing department. Written procedure will make the employees easier to know their tasks and responsibilities. Thereby, internal control on purchasing system and cash expenditure can be effective.